English teachers’ perceptions of Task-Based Instruction in Risaralda, Colombia. - Angela Patricia Velásquez Hoyos (Colombian Applied Linguistics Journal)
This paper reports the findings of the bilingualism macro-project developed in the department of Risaralda which was aimed at determining English teachers’ perceptions after the implementation of Task-Based Instruction (TBI) in this department. This project used a qualitative paradigm with a narrative inquiry orientation to analyse the experiences of 12 English language teachers implementing TBI. Classroom observations, questionnaires and interviews were the instruments used to collect data from English teachers.  The results indicated that English language educators in Risaralda find this methodology helpful to improve students’ English language skills as well as their engagement toward the English class, but they also manifest that implementing classes with TBI is time consuming and requires the design and adaptation of culture-sensitive materials. The results also report that English teachers experienced a methodological shift in their classes, changing from a structural approach to a more communicative one.